Windows XP Unwired - Lee, Wei-Meng (O'Reilly, 2011)
Windows XP Unwired provides a complete introduction to all the wireless technologies supported by Windows XP, including Wi-Fi (802.11b, a, and g), infrared, Bluetooth, CDMA2000, and GPRS. It's a one-stop wireless information source for technically savvy Windows XP users. This book will show you the full-spectrum view of wireless capabilities of Windows XP, and how to take advantage of them.